Looking for me - Hoffman, Beth. (New York : Pamela Dorman Books/Viking, 2013)
Opening an antiques shop in Charleston after discovering a talent for restoring furniture, Teddi Overman struggles to come to terms with her shattered family and sense of self after receiving news that her long-missing brother might still be alive.
Keywords: Antique dealers -- Fiction; Brothers and sisters -- Fiction; Family secrets -- Fiction; Missing persons -- Fiction; Memory -- Fiction; Domestic fiction